A NEW HYBRID ALGORITHM FOR THE MODIFIED BARRIER FUNCTION FORM - ABBAS Y. AL-BAYATI; ASEEL MOAYAD QASIM (College of Education for Pure Sciences, 2008)
Abstract In this paper, we have developed a new formula which is more suitable to the Barrier function and we have also investigated a new hybrid algorithm of SD and VM formulas with exact line search in the field of non-linear constrained optimization.